2021
DOI: 10.1021/acschemneuro.1c00575
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Sympathetic Positron Emission Tomography Imaging with Meta-[18F]Fluorobenzylguanidine is Sensitive to Uptake-1 in Rats

Abstract: Dysfunction of the cardiac sympathetic nervous system contributes to the development of cardiovascular diseases including ischemia, heart failure, and arrhythmias. Molecular imaging probes such as meta-[ 123 I]iodobenzylguanidine have demonstrated the utility of assessing neuronal integrity by targeting norepinephrine transporter (NET, uptake-1). However, current radiotracers can report only on innervation due to suboptimal kinetics and lack sensitivity to NET in rodents, precluding mechanistic studies in thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The studies showed marker retention in ex vivo measurements and temporary disappearance after pharmacological treatment. The marker distribution in the rat heart depends on NET and extra-neuronal transporters with limited reuptake into the myocardium [145]. The group shows that the obtained images show high sensitivity and higher resolution than the comparable [ 123 I]-mIBG, indicating an excellent quantitative correlation with the size of the post-infarction zone in the rat MI model.…”
Section: Ischemic Heart Diseasementioning
confidence: 92%
“…The studies showed marker retention in ex vivo measurements and temporary disappearance after pharmacological treatment. The marker distribution in the rat heart depends on NET and extra-neuronal transporters with limited reuptake into the myocardium [145]. The group shows that the obtained images show high sensitivity and higher resolution than the comparable [ 123 I]-mIBG, indicating an excellent quantitative correlation with the size of the post-infarction zone in the rat MI model.…”
Section: Ischemic Heart Diseasementioning
confidence: 92%